Prevalence of Obesity among Women Aged 45-55 Years Living in Milima Sub Location of Bungoma North District in Kenya - Wafula , Juliet (African Journal of Education,Science and Technology (AJEST), 2015)
The period of 45-55 years of age signifies the menopause transition (climacteric). This is one of the stages in a woman‘s life where overweight and onset of obesity are favored. There are few studies on Nutritional Status of menopausal women in several parts of the world including Kenya in relation to prevalence of obesity. The aim of this study was to determine the prevalence of obesity among women aged 45-55 years from Milima Sub location of Bungoma North District. This was a cross sectional study. Two hundred and twenty participants consented to participate in the study. The data was collected using anthropometric measurements where, height, waist and hip circumference and mid upper arm muscle circumference were taken using a non-stretchable tape measure to the nearest one centimeter. A skin fold caliper was used to measure triceps and biceps skin fold (SF).Weight and height were measured using a weighing scale, and a height board, respectively. Nutritional status was based on Body Mass Index (BMI) determined as (weight (Kg)/Height (m2)), waist to hip ratio (WHR) and percentage of body fat. Results showed that the mean age ±(SD), waist to hip ratio (WHR), Body mass index (BMI) and mid upper arm circumference (MUAC) of the respondents were 49.6±3, 0.88±0.8, 24.67±6.7 and 29.98±5.4, respectively. The number of women considered obese (BMI>30) and underweight (BMI<18) was (19.1%) and (18.6%) respectively. Based on waist to hip ratio (WHR) and % of body fat 36.4% and 73.9% of the study participants were found to be obese (WHR>0.9 and (percentage of body fat ≥ 38%,) respectively. It was concluded that the majority of the women aged 45-55 in Milima sub location are over nourished. The women aged 45-55 years in Milima sub location should be enlightened on weight management so as to reduce the high prevalence of obesity.